Experimental study on disproportionate permeability reduction caused by non-recovered fracturing fluids in tight oil reservoirs. (15th August 2018) - Song, Zhaojie; Hou, Jirui; Zhang, Liya; Chen, Zhiyao; Li, Meng
Highlights: Inefficient recovery of fracturing fluid leaves much chemical residual in microfractures. Higher polymer friction reducer concentration aggravated core damage. Non-recovered fracturing fluid reduced permeability to water more than to oil. The F rr exhibited a power-law characteristic through shear rate. A smaller fracture exhibited a larger residual resistance factor. Abstract: Inefficient recovery of fracturing fluid leaves much chemical residual (containing polymer friction reducer) in microfractures, which is closely related to relative permeability near fracture, flowback of fracturing fluid, production rate, etc. This work was to investigate rock damage associated with fracturing fluid filtration and its effect on subsequent oil and water flow behavior. First, fracturing fluid filtration test was performed under different core permeability and polymer friction reducer concentration conditions. Second, fractured tight sandstone models were fabricated with different fracture widths. Oil or brine was injected at various velocities before and after fractured tight sandstone models were fluxed with fracturing fluid, and residual resistance factors to oil ( F rr, oil ) and brine ( F rr, brine ) were specified with different fracture widths and polymer friction reducer concentrations. Experimental results showed that core damage occurred and polymer chains were trapped or adsorbed in rock matrix. Higher polymer friction reducer concentration would aggravate core damage in a lower permeability core sample. Residual resistance factor to brine and oil decreased as shear rate increased, and their relationship could be well fitted with a power-law equation. F rr, brine was always larger than F rr, oil, which revealed non-recovered fracturing fluid could selectively reduce the permeability to water more than to oil in microfractures. The reason behind it was elucidated by polymer wall effect. At the same shear rates, smaller fractures presented larger residual resistance factors. Besides, chemical residual grew with an increase in friction reducer concentration, resulting in a higher resistance to fluid flow. This study could provide a constructive guide for flowback after fracturing operations and the development of fracturing fluid.